Analysis of expressive illocutionary act in the movie entitled the conjuring 2 - Dewi, Ni Kadek Noviarianti Karisma; Utami, Ni Made Verayanti (Journal of Language and Applied Linguistics, 2022)
Language is one the foremost necessary ability folks use to interact with others. The fascinating phenomena in illocutionary act is the act are often use not just concerning what the speaker vocalization. The study aims to investigate the kinds of expressive illocutionary act found in the movie The conjuring 2 and also the context situation supports in the movie the conjuring 2. This study the writer used some methods there are descriptive qualitative and quantitative method. And also used some theories, first from Searle (1979) theory of types illocutionary act, Halliday and Hassan (1985) theory context situation. Based on the data, there are 32 utterances found in the movie with 6 types there are (22%) of thanking, (16%) of apologizing, (22%) of attitude, (28%) of greeting, (9%) of wishing, (3%) of congratulating and field, tenor, and mode as the context of situation found in the movie the conjuring 2.